Routine saliva testing for SARS-CoV-2 in children: Methods for partnering with community childcare centers - Rayack, Erica J.; Askari, Hibah Mahwish; Zirinsky, Elissa; Lapidus, Sarah; Sheikha, Hassan; Peno, Chikondi; Kazemi, Yasaman; Yolda-Carr, Devyn; Liu, Chen; Grubaugh, Nathan D.; Ko, Albert I.; Wyllie, Anne L.; et al. (Frontiers in Public Health, 2023)
While considerable attention was placed on SARS-CoV-2 testing and surveillance programs in the K-12 setting, younger age groups in childcare centers were largely overlooked. Childcare facilities are vital to communities, allowing parents/guardians to remain at work and providing safe environments for both children and staff. Therefore, early in the COVID-19 pandemic (October 2020), we established a PCR-based COVID-19 surveillance program in childcare facilities, testing children and staff with the goal of collecting actionable public health data and aiding communities in the progressive resumption of standard operations and ways of life. In this study we describe the development of a weekly saliva testing program and provide early results from our experience implementing this in childcare centers. We enrolled children (aged 6 months to 7 years) and staff at seven childcare facilities and trained participants in saliva collection using video chat technology. Weekly surveys were sent out to assess exposures, symptoms, and vaccination status changes. Participants submitted weekly saliva samples at school. Samples were transported to a partnering clinical laboratory or RT-PCR testing using SalivaDirect and results were uploaded to each participant's online patient portal within 24 h. SARS-CoV-2 screening and routine testing programs have focused less on the childcare population, resulting in knowledge gaps in this critical age group, especially as many are still ineligible for vaccination. SalivaDirect testing for SARS-CoV-2 provides a feasible method of asymptomatic screening and symptomatic testing for children and childcare center staff. Given the relative aversion to nasal swabs in younger age groups, an at-home saliva collection method provides an attractive alternative, especially as a routine surveillance tool. Results can be shared rapidly electronically through participants' private medical chart portals, and video chat technology allows for discussion and instruction between investigators and participants. This study fosters a cooperative partnership with participating childcare centers, parents/guardians, and staff with the goal of mitigating COVID-19 transmission in childcare centers. Age-related challenges in saliva collection can be overcome by working with parents/guardians to conceptualize new collection strategies and by offering parents/guardians continued virtual guidance and support.